2009
DOI: 10.1038/npp.2009.196
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging of Effects of a Nicotinic Agonist in Schizophrenia

Abstract: 3-(2,4-Dimethoxybenzylidene)-anabaseine (DMXB-A) is a partial agonist at α7 nicotinic acetylcholine receptors and is now in early clinical development for treatment of deficits in neurocognition and sensory gating in schizophrenia. During its initial Phase 2 test, functional magnetic resonance imaging studies were conducted to determine if the drug had its intended effect on hippocampal inhibitory interneurons. Increased hemodynamic activity in the hippocampus is found during many tasks, including smooth pursu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…In addition, DMXB-A significantly decreased hippocampal activation during a smooth pursuit eye movement task. These findings are consistent with the previously established function of a 7 -nicotinic receptors on the inhibitory interneurons in the hippocampus (Tregellas et al, 2010(Tregellas et al, , 2011.…”
Section: Neuropsychopharmacology Reviews Activation In Vivosupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, DMXB-A significantly decreased hippocampal activation during a smooth pursuit eye movement task. These findings are consistent with the previously established function of a 7 -nicotinic receptors on the inhibitory interneurons in the hippocampus (Tregellas et al, 2010(Tregellas et al, , 2011.…”
Section: Neuropsychopharmacology Reviews Activation In Vivosupporting
confidence: 93%
“…DMXB-A treatment was associated with changes in default mode activity as compared with placebo, with reductions in the posterior cingulate, inferior parietal cortex, and medial frontal gyrus, and an increase in precuneus activity. The most robust difference, specifically, reductions posterior cingulate activity, was influenced by the CHRNA7 genotype (Tregellas et al, 2010(Tregellas et al, , 2011. These results suggest normalization of default mode function, but future studies will need to include control subjects for verification of the normal default mode network.…”
Section: Neuropsychopharmacology Reviews Activation In Vivomentioning
confidence: 82%
See 1 more Smart Citation
“…A significant association of SNP rs8028396 with smoking, as well as with smoking in schizophrenia, in a non-Hispanic Caucasian population was observed (Stephens et al, 2012;Neri et al, 2012). SNP rs3087454 was first shown to be significantly associated to schizophrenia (Stephens et al, 2009) and also influenced differences in synaptic activity, as detected by functional magnetic resonance imaging, between patients with schizophrenia and control subjects performing an auditory oddball task (Tregellas et al, 2010). A Korean population-based study on the development of either schizophrenia or bipolar disorder (BD) demonstrated that SNPs rs2337506, rs6494223, and rs12916879 exhibited only a marginal association with BD (Joo et al, 2010) and that SNP rs6494223 was associated with a protective effect in BD (Ancin et al, 2010) and impaired attention in patients with euthymic bipolar disorder (Ancin et al, 2011).…”
Section: A the Chrna7 Gene And Its Variantsmentioning
confidence: 99%
“…It is possible that these prefrontal neurons are involved in P50 suppression through cholinergically mediated signals; there is in vitro evidence that cortical ACh release is inhibited by 5-HT-3 receptor activity, with a mediating role for GABA A receptors (Rámirez et al, 1996). Direct augmentation of nicotine receptor activity also restores P50 suppression in schizophrenic patients (Adler et al, 1993), and recently the partial a-7 nicotine agonist DMBX-A (150 mg, 4-weeks regime) reduced hippocampal activation in patients during smooth pursuit (Tregellas et al, 2009). …”
Section: Box 4 Human Electrophysiology As Indices Of a 'Unified Brainmentioning
confidence: 99%